Por um arquivo histórico do vinho do Porto - Pereira, Gaspar Martins (2002)
Starting from the identification and a brief characterization of the main archives connected to the Demarcated Area of Douro and to the Port wine, whose world-wide importance elapses from the interest of the regulation politics and of intervention of the State in a region of wines for the first time, it is proposed a strategy of integrated action in order to preserve, organize, gather, study and divulgate that patrimony today dispersed for several institutions, in its largest part banned to the investigators, with no organization, and, in ceratin cases, in risk. It is defended, on one side, the concentration of the archives of the entities that regulate the Port wine and of its origin area in an Historical Archive of the Port Wine, one of the nuclei foreseen to the Douro Museum according to the respective Law. Beyond its own collections, or deposited there, that archive could still undertake a set of contacts with other national and foreigner archives in order to obtain copies, in digital support, of documents important for the history of the Port wines, scattered in those archives. In relation to the families or firms archives, it is defended the release of cooperation actions between the firms of the sector, public and private institutions, academical organisms, archives, investigation centres and so on, with view to mobilize technical and human resources appropriate for the identification, preservation, study and divulgation of those collections.